Performance of Fe/SiC catalysts for cracking of toluene under microwave irradiation. (12th April 2018) - Zhang, Yuchuan; Song, Zhanlong; Yan, Yecheng; Zhao, Xiqiang; Sun, Jing; Mao, Yanpeng; Wang, Wenlong
Abstract: In this work, toluene as a model compound of biomass tar and inexpensive Fe supported on SiC powder as catalysts were used to investigate the influence of specific microwave power levels, Fe content, and space velocity on the microwave cracking of toluene. The results revealed that the microwave-aided cracking of toluene was efficient and that the composition of cracking gas was mainly H2 . During the reaction, the instantaneous cracking efficiency and the instantaneous hydrogen yield increased initially and then decreased, with the highest values being recorded as 94.4% and 89.8% at 10–12 min of the reaction. For the whole reaction, the overall cracking efficiency and the overall hydrogen yield reached maximum (86.3% and 84.5%, respectively) when the tests were conducted under the optimum conditions. The catalysts before and after reaction were analyzed by scanning electron microscopy-energy dispersive spectrometer (SEM-EDS), thermogravimetry (TG), X-ray diffraction (XRD), and temperature programmed oxidation (TPO). The results confirmed that the deposited carbon included spherical and filamentous carbon and carbon deposition yield could reach 2.3%, which had a negative effect on the cracking of toluene. Highlights: Microwave cracking of toluene over Fe/SiC catalysts was efficient. The composition of cracking gas of toluene was mainly H2 . The highest cracking efficiency (86.3%) and H2 production yield (84.5%) were achieved. Deposited carbon were spherical and filamentous with carbon deposition yield of 2.3%.